Preservation assessments on digital cultural heritage resources in Malaysia / Noor Masliana Razlan...[et al.] - Razlan, Noor Masliana; Ismail, Mohd Nasir; Abd Manaf, Zuraidah; Abdullah, Nurulannisa (2015)
Cultural heritage is crucial to the nation’s development. A crucial component of the nation’s K‐economy envisions the availability of digital content exchange or content infrastructure. Digitization makes the cultural heritage resources accessible since the openness of the internet causes the resources to be available to the wide audience. The idea of providing and presenting information via electronic means and formats truly fascinates managers of information agencies worldwide. People especially the professionals are quite serious in preserving our national culture heritage because of the awareness of its importance to our legacy. Most of national cultural heritage institutions are seeing a move from the hegemony of the physical records to the hegemony of the digital objects. Therefore, the aim of this paper is to assess potential risks of digital cultural resources in Malaysia as well as to investigate the digital preservation strategies adopted by Malaysian cultural institutions. A multiple case studies approach is used to examine the potential risks of digital cultural resources in four (4) selected Malaysian cultural institutions. Data is collected through a structured interview with information professionals who are involved in digitization works in the selected cultural institutions. Findings reveal that digital cultural heritage resources in Malaysia are at risk in terms of digitization policies, selection criteria, cost, staffing, technology, storage, metadata management and copyrights. This study is very significant to professionals who are involved in archiving the digital cultural heritage as it serves as a guide for managing risks in the process of preserving valuable digital resources. The result can be a practical tool for preservation assessments of not only digital cultural heritage but also to any format of digital documents in various fields or industries.